2017
DOI: 10.1093/gbe/evx195
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomics of Steinernema and Caenorhabditis Single Embryos Reveals Orthologous Gene Expression Convergence during Late Embryogenesis

Abstract: Cells express distinct sets of genes in a precise spatio-temporal manner during embryonic development. There is a wealth of information on the deterministic embryonic development of Caenorhabditis elegans, but much less is known about embryonic development in nematodes from other taxa, especially at the molecular level. We are interested in insect pathogenic nematodes from the genus Steinernema as models of parasitism and symbiosis as well as a satellite model for evolution in comparison to C. elegans. To expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…However, genes that originated in the early metazoan lineage and with the ecdysozoan superphylum are expressed during the middevelopmental transition. We further tested this result by examining the expression of genes of different ages in the recently published developmental transcriptome of the parasitic clade IV species Steinernema carpocapsae (43). Again, we found the same pattern ( Fig.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…However, genes that originated in the early metazoan lineage and with the ecdysozoan superphylum are expressed during the middevelopmental transition. We further tested this result by examining the expression of genes of different ages in the recently published developmental transcriptome of the parasitic clade IV species Steinernema carpocapsae (43). Again, we found the same pattern ( Fig.…”
Section: Resultsmentioning
confidence: 52%
“…study examining the developmental transcriptomes of the parasitic clade IV species S. carpocapsae (43). Our phylostratigraphical analysis shows that genes that emerged during the origin of the superphylum Ecdysozoa and the Nematoda are more conserved in their developmental expression.…”
Section: Discussionmentioning
confidence: 87%
“…A conserved profile of developmental gene expression was observed in several studies across animal phyla, including in non-bilaterians, when developmental time course data were analyzed [ 12 ]. These studies suggest the existence of a phylotypic stage late in development, but see [ 12 , 48 , 62 ]. We observed low expression of young genes that originated after the emergence of Bilateria and of set genes in early development.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of early embryonic transcripts across many Drosophila species and the mosquito Aedes aegypti has revealed that maternal transcript pools that, like those of C. elegans skn-1, are present only transiently during early embryogenesis, and that their expression levels are highly variable across these species, spanning ∼60 million years of evolution (Atallah and Lott, 2018). Similarly, considerable variation in the expression of maternal factor genes is found between different nematode species (Levin et al, 2012;Macchietto et al, 2017;Schiffer et al, 2018). This hourglass pattern of variation is attributable to the lack of negative selection of maternal-effect genes (Barker et al, 2005;Cruickshank and Wade, 2008;Cutter et al, 2019), as well as to increased developmental constraints during mid-embryogenesis (Raff, 1996;Zalts and Yanai, 2017).…”
Section: Developmental Hourglass Model: Plasticity and Conservation Omentioning
confidence: 99%